Consumer Decision Model of Intelectual Property Theft in Emerging Markets - Lalović, Gordana; Reardon, Saule Amirebayeva; Vida, Irena; Reardon, James (Organizations and Markets in Emerging Economies, 2012)
The increasing importance of digital piracy has prompted research on the behavioural and economics origins of illegal downloading activities. This research focuses on the potential impact of various economic, psychological and social factors on the consumer decision whether to buy or to steal music in emerging markets. These markets present specific difficulties for owners of intellectual property rights due to the high level of both downloading and ‘sharing’ of digital property. Results indicate impacts of price, downloaded music quality, ease of Internet use, attitudes toward music industry and ethical perception of music downloading on consumer purchase or pirate decision.